2005
DOI: 10.1096/fj.04-2870fje
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber‐specific apoptosis and TNF‐α signaling in sarcopenia are attenuated by life‐long calorie restriction

Abstract: Increased tumor necrosis factor-alpha (TNF-alpha) levels have been found with age and are connected to muscle atrophy and cell loss, yet the signaling events that occur in vivo are unknown. Calorie restriction (CR), a robust intervention shown to repeatedly evade the physiological declines associated with aging, has been reported to reduce TNF-alpha and may assist in understanding the mechanisms of muscle sarcopenia. The effects of age and CR on muscle mass, myocyte area, fiber number, myocyte TNF-alpha expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
217
4
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(240 citation statements)
references
References 57 publications
17
217
4
2
Order By: Relevance
“…Our observations of potential muscle and/or fiber type specific differences in TNF-α associated apoptotic signaling differs from data reported by Phillips and Leeuwenburgh [25], who did not find differences in the expression of apoptotic markers between the soleus (primarily a type I fibered muscle) and the superficial vastus lateralis muscles (primarily a type II fibered muscle) of aged rats. These disparate findings may be due to the different strains and ages of rodents utilized in our study and the previous study [25].…”
Section: Type II Muscle Fibers and Agingcontrasting
confidence: 99%
See 2 more Smart Citations
“…Our observations of potential muscle and/or fiber type specific differences in TNF-α associated apoptotic signaling differs from data reported by Phillips and Leeuwenburgh [25], who did not find differences in the expression of apoptotic markers between the soleus (primarily a type I fibered muscle) and the superficial vastus lateralis muscles (primarily a type II fibered muscle) of aged rats. These disparate findings may be due to the different strains and ages of rodents utilized in our study and the previous study [25].…”
Section: Type II Muscle Fibers and Agingcontrasting
confidence: 99%
“…These disparate findings may be due to the different strains and ages of rodents utilized in our study and the previous study [25]. Despite these differences, the data from our study and that of Phillips and Leeuwenburgh [25] suggest that the extrinsic apoptotic pathway is active in skeletal muscle of aged rodents and this may contribute to age-associated muscle loss via increases in apoptotic signaling.…”
Section: Type II Muscle Fibers and Agingcontrasting
confidence: 62%
See 1 more Smart Citation
“…An alternative possibility is that CR activates Sirt1, which then deacetylases components of the NF-κB complex (Yeung et al, 2004b;Ghosh et al, 2007;Salminen et al, 2008; but see Barger et al, 2008). Previous studies have indeed found that NF-κB signaling is inhibited by caloric restriction in both rodents and humans (Phillips and Leeuwenburgh, 2005;Dirks and Leeuwenburgh, 2006;Weiss et al, 2006;Ugochukwu and Figgers, 2007), and that inhibition of NF-κB blocks the accumulation of beta-amyloid plaques in Alzheimer's mice (Paris et al, 2007), as well as neoplastic transformation of cells during the initial stages of cancer (Karin, 2006). Such effects result from blocking NF-κB activation, which is a characteristic feature of normal aging, as demonstrated by a recent genomic study (Adler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the death receptor-mediated pathway, triggered by TNF-α, is thought to play a significant role in age-related muscle loss [14,17,19,20], owing to its ability to promote muscle protein wasting [63,64] and myonuclear apoptosis [14,17,19,20,65]. Interestingly, the transduction of TNF- α signaling during aging may be fiber-type specific[14]. In fact, TNF- α-mediated apoptosis was enhanced at old age in the rat superficial vastus lateralis muscle (predominantly comprised of type II fibers), whereas increased signaling through the NF-κB pathway was observed in the soleus muscle, characterized by type I fiber dominance.…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 99%